Pengaruh Transformasi Digital terhadap Efektivitas MSDM di Era Industri 4.0 - Dita Zahra Aprillianti; Wulandari, Yunika Putri; Mahfud Mahfud; Bangun, Scivo Orlando (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2025)
Digital transformation in the Industry 4.0 era significantly impacts the effectiveness of human resource management (HRM). This article discusses the impact of digital transformation on HRM, focusing on changing roles, developing digital skills, and utilizing technology for more effective and efficient decision-making. In the past, HRM focused on administrative aspects, but now, there is a demand to develop digital skills for employees in response to modern workplace dynamics. Digital competencies are becoming essential and contributing to increased productivity and organizational competitiveness. This transformation requires a more adaptive competency-based approach to ensure employees have skills relevant to technological developments. HR management facilitates this adaptation through appropriate training and technology implementation in data-driven decision-making processes. By doing so, organizations can respond to challenges and take advantage of new opportunities in the digital era. The World Economic Forum (2020) emphasizes that digital skills, such as technological understanding, data analysis, and digital device proficiency, are now an essential foundation for competitiveness in the modern job market. With the paradigm shift from an administrative function to a strategic role, innovative leadership is required for HRM to support organizational success in the face of Industry 4.0.